2011
DOI: 10.1074/jbc.m110.217349
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inhibition of Pyruvate Dehydrogenase in Heart Triggers an Adaptive Metabolic Response

Abstract: Diabetic cardiac dysfunction is associated with decreased rates of myocardial glucose oxidation (GO) and increased fatty acid oxidation (FAO), a fuel shift that has been shown to sensitize the heart to ischemic insult and ventricular dysfunction. We sought to evaluate the metabolic and functional consequences of chronic suppression of GO in heart as modeled by transgenic mice with cardiac-specific overexpression of pyruvate dehydrogenase kinase 4 (myosin heavy chain (MHC)-PDK4 mice), an inhibitor of pyruvate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 41 publications
6
71
0
Order By: Relevance
“…However, transcriptional analysis revealed that PDK4 was highly upregulated in hearts of HFD- fed WT animals ( Figure 1B and Supplemental Figure 9B). PDK4 is believed to function as a metabolic switch, shifting the cell toward FA utilization and away from glycolysis (5,16,(18)(19)(20). Loss of FoxO1 blunted PDK4 gene expression (Supplemental Figure 5 and Supplemental Figure 9B), a finding consistent with PDK4's being a known FoxO1 gene target (5,18,19).…”
Section: Figuresupporting
confidence: 71%
See 1 more Smart Citation
“…However, transcriptional analysis revealed that PDK4 was highly upregulated in hearts of HFD- fed WT animals ( Figure 1B and Supplemental Figure 9B). PDK4 is believed to function as a metabolic switch, shifting the cell toward FA utilization and away from glycolysis (5,16,(18)(19)(20). Loss of FoxO1 blunted PDK4 gene expression (Supplemental Figure 5 and Supplemental Figure 9B), a finding consistent with PDK4's being a known FoxO1 gene target (5,18,19).…”
Section: Figuresupporting
confidence: 71%
“…Loss of FoxO1 blunted PDK4 gene expression (Supplemental Figure 5 and Supplemental Figure 9B), a finding consistent with PDK4's being a known FoxO1 gene target (5,18,19). However, it is unlikely that the entire cardiomyopathic response to HFD derives from PDK4 gene upregulation and resulting shifts in metabolic substrate utilization, as a cardiomyocyte-specific transgenic mouse line over-expressing PDK4 was not marked by apparent cardiomyopathy (18,20). FoxO1-dependent downregulation of IRS1 activity.…”
Section: Figuresupporting
confidence: 48%
“…A total of 3 ϫ 10 4 cells were plated per well of a 96-well plate and transfected with the PGL3.Luc vector, carrying a 2,760-bp fragment of the human PPARGC1␣ promoter (for firefly luciferase expression), and the pRL-SV40 vector (for Renilla luciferase expression [31]) at a 100:1 ratio, using Lipofectamine 2000 (Invitrogen). Constructs coding for the human PPARGC1␣ promoter (GenBank accession number NG_028250.1) with individual mutations in the three CLEAR sites detected within (as depicted in Fig.…”
mentioning
confidence: 99%
“…For example, fenofibrate increases cardiac mitochondrial thioesterase I (MTE-I) mRNA, and reduced acyl-CoA oxidase (ACO) activity in diet-induced obese (DIO) mice (33,34). All the altered expression of these genes involved in cardiac mitochondrial function is coupled to a change in glucose utilization and fatty acid oxidation (35). Indeed, reduced ACO activity is linked to increased glucose oxidation and decreased fatty acid oxidation (34), and our studies also showed that downregulation of PGC-1α by fenofibrate is coupled to myocardial lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%